Protein N-Terminal Acetylation: Structural Basis, Mechanism, Versatility, and Regulation - Deng, Sunbin; Marmorstein, Ronen (Trends in biochemical sciences (Amsterdam. Regular ed.), 2021)
N-terminal acetylation (NTA) is one of the most widespread protein modifications, which occurs on most eukaryotic proteins, but is significantly less common on bacterial and archaea proteins. This modification is carried out by a family of enzymes called N-terminal acetyltransferases (NATs). To date, 12 NATs have been identified, harboring different composition, substrate specificity, and in some cases, modes of regulation. Recent structural and biochemical analysis of NAT proteins allows for a comparison of their molecular mechanisms and modes of regulation, which are described here. Although sharing an evolutionarily conserved fold and related catalytic mechanism, each catalytic subunit uses unique elements to mediate substrate-specific activity, and use NAT-type specific auxiliary and regulatory subunits, for their cellular functions. To date, a total of 12 different NATs have been identified, to collectively N-terminally acetylate countless proteins from all domains of life, to mediate many biological processes.NATs uniquely mediate both post- and co-translational N-terminal acetylation.The currently availability of structures of many NATs bound to their cognate substrates, now allows for a detailed molecular comparison to derive conserved and unique features, underlying NAT activity and substrate specificity.NATs are subject to regulation by inhibitor and stimulatory proteins, and the molecular basis for this regulation has recently come to light